Neutrophils: Need for Standardized Nomenclature - McKenna, Ellen; Mhaonaigh, Aisling Ui; Wubben, Richard; Dwivedi, Amrita; Hurley, Tim; Kelly, Lynne A.; Stevenson, Nigel J.; Little, Mark A.; Molloy, Eleanor J. (Frontiers in Immunology, 2021)
Neutrophils are the most abundant innate immune cell with critical anti-microbial functions. Since the discovery of granulocytes at the end of the nineteenth century, the cells have been given many names including phagocytes, polymorphonuclear neutrophils (PMN), granulocytic myeloid derived suppressor cells (G-MDSC), low density neutrophils (LDN) and tumour associated neutrophils (TANS). This lack of standardised nomenclature for neutrophils suggest that biologically distinct populations of neutrophils exist, particularly in disease, when in fact these may simply be a manifestation of the plasticity of the neutrophil as opposed to unique populations. In this review, we profile the surface markers and granule expression of each stage of granulopoiesis to offer insight into how each stage of maturity may be identified. We also highlight the remarkable surface marker expression profiles between the supposed neutrophil populations.